PENERAPAN KAHOOT DAN SPINNER SEBAGAI UPAYA INTEGRASI TEKNOLOGI DALAM PEMBELAJARAN : - - Siti Niah; Prih Febtiningsih; Pahmi Pahmi; Ardiya Ardiya; Wandi Syahfutra; Qonaan Nuryan Arif; Esti Raihana (Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
The integration of technology in education plays a crucial role in enhancing teachers’ competence and improving educational quality in the digital era. However, teachers at SMK Darel Hikmah Pekanbaru have not yet fully optimized technology integration in their teaching practices. This community service project aimed to enhance teachers’ competence through training on the use of Kahoot and Spinner as interactive, gamified learning tools. The one-day training employed tutorials, discussions, and hands-on activities involving 20 teachers. Evaluation using a Likert-scale questionnaire revealed that 95% of participants understood Kahoot and 90% felt confident applying Spinner in their classrooms. The program effectively improved teachers’ understanding and skills in implementing innovative and engaging technology-based teaching methods.